2022
DOI: 10.21037/apm-22-1204
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of vascular access among hemodialysis unit nurses and its influencing factors: a cross-sectional study

Abstract: Background: Nurses in hemodialysis (HD) units are the main performers in the maintenance and management of HD patients' vascular access, and the cognition degree of their specialized knowledge of vascular access directly affects the quality of vascular access management. However, most of the investigations on the cognition of vascular access knowledge take HD patients as the research subjects, while there are few studies on nurses in HD units as the research subjects. Herein, we explored the knowledge of vascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…This disparity can be attributed to variations in management policies and nursing practices. [22] Based on our study findings we suggest several recommendations for improving VA management among hemodialysis nurses in Saudi Arabia. These include giving priority to specialized training programs, implementing ongoing training initiatives focused on VA management, and addressing knowledge gaps related to complications and proper cannulation techniques.…”
Section: Questionmentioning
confidence: 72%
See 4 more Smart Citations
“…This disparity can be attributed to variations in management policies and nursing practices. [22] Based on our study findings we suggest several recommendations for improving VA management among hemodialysis nurses in Saudi Arabia. These include giving priority to specialized training programs, implementing ongoing training initiatives focused on VA management, and addressing knowledge gaps related to complications and proper cannulation techniques.…”
Section: Questionmentioning
confidence: 72%
“…Furthermore, participants reported receiving adequate training and supervision in the early stages of their careers as dialysis nurses prior to performing cannulation procedures. [ 22 ] This highlights the crucial role of specialized training for hemodialysis nurses, as emphasized by 93.0% of participants. Additionally, the study revealed a notable positive attitude toward the cannulation and management of dialysis VA.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations